Effect of bimekizumab on symptoms and impact of disease in patients with psoriatic arthritis over 3 years: results from BE ACTIVE. (5th July 2022) - Mease, Philip J; Asahina, Akihiko; Gladman, Dafna D; Tanaka, Yoshiya; Tillett, William; Ink, Barbara; Assudani, Deepak; de la Loge, Christine; Coarse, Jason; Eells, Jason; Gossec, Laure
Abstract: Objectives: Evaluate effects of long-term bimekizumab treatment on patient-reported outcome (PRO) measures, symptoms and the impact of PsA on patients. Methods: Patients with active PsA were enrolled into BE ACTIVE, a 48-week randomised controlled trial (NCT02969525). After Week 48, patients could enter a 104-week open-label extension (NCT03347110), receiving bimekizumab 160 mg every four weeks. PRO measures assessed included arthritis pain visual analogue scale (VAS), PsA Impact of Disease (PsAID)-9, 36-Item Short Form Survey (SF-36) and HAQ-Disability Index (HAQ-DI). Results were analysed as mean (S.E.M.) changes from baseline (CfB) from Week 0 to the end of the open-label extension (3 years) and as percentage of patients reaching patient-acceptable symptom state (PASS) for global impact (PsAID-9 total score ≤4) and normal function (HAQ-DI total score <0.5). Non-responder imputation was applied to missing binary outcomes. Results: In 206 patients (mean age 49.3 years, 51.0% male), completion rate was high; 161 (78.2%) patients completed Week 152. Bimekizumab treatment was associated with long-term sustained improvements in pain [arthritis pain VAS CfB; Week 48: −29.9 (1.9); Week 152: −32.0 (1.9)] and fatigue [PsAID-9 fatigue CfB; −2.4 (0.2); −2.7 (0.2)]. High percentages of patients achieved acceptable symptom state (PsAID-9 PASS: 75.2%; 65.0%) and normalised function (HAQ-DI <0.5: 49.0%; 46.1%). Improvements in patient global assessment and SF-36 Physical Component Summary were also sustained. Conclusions: Bimekizumab treatment was associated with long-term sustained improvements in pain and fatigue, reducing overall impact of PsA on patients. Physical function and quality of life improved up to 3 years. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT02969525, NCT03347110. Graphical Abstract: